Chitosan microparticles loaded with essential oils having in view leather applications - Fernandes, I.P. (2011)
Chitosan is a biopolymer attracting considerable attention for diverse applications due to its unique properties like biodegradability, biocompability, non-toxicity and antimicrobial activity. It is obtained by the partial N-deacetylation of chitin, which is the second most abundant polysaccharide in nature, next to cellulose. Chitosan is a viable base material for functional coatings development, namely due to its antimicrobial activity. This characteristic is especially useful for footwear applications that constitute products prone to microbial attack. In this context, developing antimicrobial coatings to be used in footwear components in direct contact with the feet are of great interest, both at industrial level (reducing possibility of material deterioration and quality loss), as well as, from the consumer’s point of view (decrease of skin infections and minor unpleasant odours). Following our previous work, where leather impregnation with chitosan was studied at laboratorial level with quite promising results, and having in view the final application (footwear leather components), where the antimicrobial effect must need to be enhanced, we have developed the idea of microencapsulate different essential oils, with recognized antimicrobial activity like lemon, oregano, eucalyptus and pine. These chitosan-based microparticles, loaded with the chosen essential oil are intended to be applied conjunctly with the chitosan coating process previously studied. Microencapsulation will ensure that the loaded core material will be progressively released, reinforcing the antimicrobial durability and effectiveness of the final product.